2013
DOI: 10.7897/2230-8407.04309
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Quinazolinone Derivatives as Marker for Various Biological Activities

Abstract: Heterocyclic chemistry comprises at least half of all organic chemistry research worldwide. Quinazolinone and its derivatives constitute an important class of heterocyclic compounds. The chemistry of quinazoline compounds has more than centuries old history; however the intense search for biologically active substances in this series began only in the last few decades. In this present communication an attempt is made to cover the medicinally active compounds, along with the recent discoveries, which were repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…From these preliminary in vitro cytotoxicity results and SAR, it is observed that a bulky group at the 9-position of the 5-styryltetrazolo[1,5- c ]quinazoline moiety generally leads to loss of cytotoxicity. The observed cytotoxicity of 3a and 3b is due to the presence of a halide or small hydrophobic substituents at position 9 in analogy with the literature observation for the analogous styrylquinazolinones [ 7 , 13 , 14 ]. The 6-substituted 2-styrylquinazoline derivatives have been found to exhibit antimitotic properties and to inhibit tubulin polymerization [ 13 ].…”
Section: Resultssupporting
confidence: 83%
“…From these preliminary in vitro cytotoxicity results and SAR, it is observed that a bulky group at the 9-position of the 5-styryltetrazolo[1,5- c ]quinazoline moiety generally leads to loss of cytotoxicity. The observed cytotoxicity of 3a and 3b is due to the presence of a halide or small hydrophobic substituents at position 9 in analogy with the literature observation for the analogous styrylquinazolinones [ 7 , 13 , 14 ]. The 6-substituted 2-styrylquinazoline derivatives have been found to exhibit antimitotic properties and to inhibit tubulin polymerization [ 13 ].…”
Section: Resultssupporting
confidence: 83%
“…The analogous ( E )-3-(3-carboxyphenyl)-2-(4-cyanostyryl)quinazolin-4(3 H )-one ( 2 ) is an effective antibiotic in vivo against methicillin-resistant Staphylococcus aureus (MRSA) and it inhibits cell wall biosynthesis by binding to DD-transpeptidases involved in cross-linking of the cell wall [9]. Extensive structure activity relationship studies on the 3-substituted 2-styrylquinazolin-4(3 H )-ones revealed that the entire styrylquinazolin-4(3 H )-one scaffold was required for inhibition of tubulin polymerization [7] and for antimicrobial activity [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although many attractive procedures have been developed for rapid access to quinazolinones,2a,b, 3, 5 the related synthesis of pyridoquinazolones is still very limited. So far, known procedures require a high temperature (210 °C), multistep synthesis, or specific ortho ‐halogen‐substituted benzoyl derivatives as the substrates 6.…”
Section: Model Synthesis Of Pyridoquinazolones: Optimization Of the Rmentioning
confidence: 99%